Board informal hierarchy, strategic aggressiveness, and corporate ESG performance - Jinye Xu; Yuanjie Xiao (PLoS ONE, 2025)
Based on the stakeholder theory, relationship contract theory, and other theories, this study examined how the board informal hierarchy influences corporate ESG (Environmental, Social, and Governance) performance, using Chinese A-share listed enterprises from 2010 to 2022 as the research samples. The results indicated that the clearer the board informal hierarchy, the better the corporate ESG performance. Furthermore, the board informal hierarchy can enhance the ESG performance by promoting more aggressive strategic initiatives. In situations characterized by high environmental uncertainty, heavy pollution industries, and state-owned enterprises, the positive impact of the board informal hierarchy on the corporate ESG performance is even stronger. This study provided a new perspective on the factors influencing the corporate ESG performance by examining the micro-level vertical structure within the board, enriching the content of ESG-related research.